IPRaDA: Transforming potato value chain in Ethiopia - International Potato Center (International Potato Center, 2023)
Ethiopia is on the cusp of a transformative shift in potato farming that promises sustainable growth and development. The Irish Potato Research and Development Association, or IPRaDA, leads this charge. In this blog, we delve into the origins, objectives, and aspirations of IPRaDA, a coalition poised to uplift the lives of potato farmers in Ethiopia.